2021
DOI: 10.4194/1303-2712-v21_9_05
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological, Haematological and Biochemical Indices of Clarias gariepinus (Burchell, 1822) Parasitized by Endoparasitic Fauna in Fish Farm of the Northeastern Egypt

Abstract: Knowledge of the endemic fauna of parasites in fish are of great importance, parasites could synergistically act as stressors to health of their hosts. The objectives of this study were to evaluate prevalence and effect of parasites on hematological, biochemical indices, injury of tissues and length weight relationship of Clarias, gariepinus. Water quality variables were measured and fishes were collected each seasons for examination most common parasites in infected fishes at Abbasa Fish Farm, Egypt. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…Total ammonia was also found to be higher in fish farms than in lakes, which might be due to large fish stocks, fish excretion, and the breakdown of extra un-consumed diet, all of which are ammonia sources in ponds. These findings corroborate previous research (Konsowa, 2007;Radwan et al, 2021;Radwan, 2022).…”
Section: Discussion Water Quality and Fish Parasites Relationshipsupporting
confidence: 93%
See 2 more Smart Citations
“…Total ammonia was also found to be higher in fish farms than in lakes, which might be due to large fish stocks, fish excretion, and the breakdown of extra un-consumed diet, all of which are ammonia sources in ponds. These findings corroborate previous research (Konsowa, 2007;Radwan et al, 2021;Radwan, 2022).…”
Section: Discussion Water Quality and Fish Parasites Relationshipsupporting
confidence: 93%
“…Dissolved oxygen and pH, on the other hand, displayed a strong negative relation with the Parasites Prevalence (PP) in lake and farmed Nile Tilapia. This observation agrees with Zargar et al (2012) and Radwan et al (2021) who observed strong negative relationships between parasite presence frequency and pH and DO concentrations. Meanwhile, these findings contradict the findings of Sosanya (2002) who found a positive relationship between water contaminants and parasite prevalence rates.…”
Section: Discussion Water Quality and Fish Parasites Relationshipsupporting
confidence: 92%
See 1 more Smart Citation
“…Egyptian expansion in fish aquaculture requires improvement in fish health management, (Al Malki , 2021). Knowledge of endemic fauna of helminths in fish is of great importance, parasites act as stressors to the health of their hosts, (Radwan et al 2021). Parasitic infection in fish is prevalent all over the world and of particular importance in tropical areas (Soliman & Nasr, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In general, hematological investigations are utilized in human and veterinary studies to assess normal vital signs and to diagnose disorders resulting from a variety of causes, including environmental stress, metal pollution, parasite infections, nutrition, and the genotoxic impact of pollutants (Esmaeili, 2021). Fish blood is susceptible to pollution-induced damage, and alternations in hematological markers, including packed cell volume, erythrocyte count, and hemoglobin concentration, may be employed to detect damage induced by pollutants, including heavy metals (Radwan et al, 2021). Biochemical markers in fish are also sensitive to possible adverse effects of metal accumulations.…”
Section: Introductionmentioning
confidence: 99%